52.5k views
22 votes
Check whether the following equation is quadratic equation:-
x²-4x-x+1=(x-2)³​

User Thetacom
by
4.7k points

2 Answers

6 votes


\Large \underline{\tt Solution} :


\tt \dashrightarrow x^2 - 4x - x + 1 = (x-2)^3


\\

By using identity :


  • \large \underline{\boxed{\bf{(a-b)^3 = a^3 - b^3 -3a^2b + 3ab^2}}}


\tt \dashrightarrow x^2 - 5x + 1 = (x)^3 - (2)^3 - 3(x)^2 (2) + 3(x)(2)^2


\tt \dashrightarrow x^2 - 5x + 1 = x^3 - 8 - 6x^2 + 3x * 4


\tt \dashrightarrow x^2 - 5x + 1 = x^3 - 8 - 6x^2 + 12x


\tt \dashrightarrow x^2 - 5x + 1 - x^3 + 8 + 6x^2 - 12x = 0


\tt \dashrightarrow - x^3 + 7x^2 - 17x + 9 = 0


\\

As, it isn't in form of ax² + bx + c = 0,

Therefore it isn't quadratic equation.

User Sirksel
by
4.3k points
12 votes

Answer:

Solve for x by simplifying both sides of the equation, then isolating the variable.

x≈−0.47082385

image of graph

Explanation:

Hope it is helpful...

Check whether the following equation is quadratic equation:- x²-4x-x+1=(x-2)³​-example-1
Check whether the following equation is quadratic equation:- x²-4x-x+1=(x-2)³​-example-2
User Aaz
by
4.8k points